Economic impact analysis of the creative gastronomy industry in Central Java on Indonesia's economy - Shanty Oktavilia,; Firmansyah,; Suharno,; Fafurida,; Yozi Aulia Rahman,; Ryan Prayogi,; Nadia Damayanti, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The creative industry is crucial for the modern economy, providing products and services with economic, cultural, and social values. A rapidly growing subsector is the gastronomy industry, which includes food and beverage preparation, presentation, and meaning. This study examines the contribution of the creative gastronomy industry to the economy of Central Java Province and Indonesia by using input-output (I-O) analysis and interregional I-O tables. This research explores intersectoral economic linkages and assesses direct and indirect economic impacts. Results show that Central Java’s gastronomy industry supports regional economic growth and income generation. It also strengthens related sectors, such as food crops, food and beverage manufacturing, wholesale and retail trade, livestock, plantations, fisheries, horticulture, and land transportation. Spatially, the culinary sector in Central Java is closely connected with regions across Java Island, particularly East Java, and relies on agricultural input from outside of Java, such as fishery products from Central Sulawesi and plantation products from Bengkulu. This study aims to provide information about strategic policymaking to support the sustainable development of the creative gastronomy industry in Central Java and beyond.